2019
DOI: 10.3389/fnagi.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Aging, and Cellular Health: Aged-Related Changes in Sleep and Protein Homeostasis Converge in Neurodegenerative Diseases

Abstract: Many neurodegenerative diseases manifest in an overall aged population, the pathology of which is hallmarked by abnormal protein aggregation. It is known that across aging, sleep quality becomes less efficient and protein homeostatic regulatory mechanisms deteriorate. There is a known relationship between extended wakefulness and poorly consolidated sleep and an increase in cellular stress. In an aged population, when sleep is chronically poor, and proteostatic regulatory mechanisms are less efficient, the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 126 publications
0
10
0
2
Order By: Relevance
“…The vervet model may be useful to address several gaps in knowledge about factors that promote or protect from LOAD. For example, several lifestyle factors including sleep (Brzecka et al, 2018; Bubu et al, 2017; Hafycz & Naidoo, 2019; Mander et al, 2016; Mander, 2020; Phan & Malkani, 2019), social isolation (Evans et al, 2019; Friedler et al, 2015; National Academies of Sciences, Engineering & Medicine, 2020; Shankar et al, 2013), impaired peripheral glucose metabolism (An et al, 2018; Craft, 2012; Ferreira et al, 2018), and gut dysbiosis (Askarova et al, 2020; Kowalski & Mulak, 2019) have been suggested to increase the risk for developing AD. However, whether any of these factors are causal remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vervet model may be useful to address several gaps in knowledge about factors that promote or protect from LOAD. For example, several lifestyle factors including sleep (Brzecka et al, 2018; Bubu et al, 2017; Hafycz & Naidoo, 2019; Mander et al, 2016; Mander, 2020; Phan & Malkani, 2019), social isolation (Evans et al, 2019; Friedler et al, 2015; National Academies of Sciences, Engineering & Medicine, 2020; Shankar et al, 2013), impaired peripheral glucose metabolism (An et al, 2018; Craft, 2012; Ferreira et al, 2018), and gut dysbiosis (Askarova et al, 2020; Kowalski & Mulak, 2019) have been suggested to increase the risk for developing AD. However, whether any of these factors are causal remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The vervet model may be useful to address several gaps in knowledge about factors that promote or protect from LOAD. For example, several lifestyle factors including sleep (Brzecka et al, 2018;Bubu et al, 2017;Hafycz & Naidoo, 2019;Mander et al, 2016;Mander, 2020;Phan & Malkani, 2019), social isolation (Evans et al, 2019;Friedler et al, 2015; National Academies of Sciences,…”
Section: Gaps In Knowledge and Future Directionsmentioning
confidence: 99%
“…K, L Quantification of the amplitude of wheel-running activity and period length from the experiment shown in (I), (J), including pre-treatment, during treatment and post-drug treatment. Proteome imbalance is already very strongly, and in some cases causally, linked to a range of pathological conditions including chronic inflammation, various cancers, metabolic disorders and neurodegeneration (Yalcin & Hotamisligil, 2013;Agyemang et al, 2015;Labbadia & Morimoto, 2015;Harper & Bennett, 2016;Hadizadeh Esfahani et al, 2018;Hafycz & Naidoo, 2019;Costa-Mattioli & Walter, 2020;Yerbury et al, 2020). It is therefore quite plausible that proteome imbalance underlies the diverse range of phenotypes exhibited by CKO mice, including impaired body growth (Masuki et al, 2005;Bur et al, 2009), increased susceptibility to multiple cancers (Lee et al, 2010;Kettner et al, 2016;Mteyrek et al, 2017;, chronic inflammation (Narasimamurthy et al, 2012;Hand et al, 2016;Cao et al, 2017) and dysregulated insulin secretion/fat deposition on high fat diets (Barclay et al, 2013).…”
Section: Cry Defends Cellular Homeostasis Which Is Permissive For Robust Circadian Rhythmsmentioning
confidence: 99%
“…The dysregulation of circadian clocks contributes to the decline in optimal functioning of the nervous system, ultimately leading to a reduction in the quality of life due to cognitive impairments and emotional stress (Touitou and Haus, 2000; Hastings et al, 2003; Hafycz and Naidoo, 2019). Therefore, since damaged circadian rhythms and sleep/wake cycles have been associated with an increase in disease susceptibility (Hastings et al, 2003; Gibson et al, 2009) it is important to determine the rather complex source of age-related circadian or sleep/wake dysfunction.…”
Section: Introductionmentioning
confidence: 99%